Mediating Effects of Future Orientation on Self- Regulation and Suicide Behaviors Among Filipino Youth - Lazaro, Rosdy; Balila, Edwin; Castillo, Sheryll Ann (12th International Scholars Conference 2025, 2026)
Suicide remains a leading cause of death for adolescents and young adults, calling for deeper understanding ofinternal protective mechanisms, where psychiatric nurses play a crucial role in community prevention. Groundedin Self-Regulation Theory and Time Perspective Theory, this descriptive-correlational study examined therelationship between self-regulation (SR), future orientation (FO), and suicidality (SUI) in a sample of 653 collegestudents randomly selected from five state-funded universities in CALABARZON, Philippines. Participants reported high levels of self-regulation, particularly in goal attainment (M = 4.08, SD = 0.56) and proactiveness (M = 4.04, SD = 0.49), along with low levels of suicidality—hopelessness (M = 2.02, SD = 0.50) and suicide ideation (M = 1.72, SD = 0.75). Pearson correlations revealed that SR was significantly and inversely associatedwith SUI (r = –.332, p < .001), while positively correlated with FO (r = .686, p < .001). Regression analysis identified proactiveness, goal attainment, and adjustment as predictors of lowerSUI, while mindfulness, goal setting, and goal attainment predicted stronger FO. Mediation analysis confirmed that FO significantly mediated the SR–SUI relationship, highlighting the protective value of future-focused thinking. ANOVA showed that mental health issues (p < .001) and gender (p < .01) significantly influenced SUI, whereas age and socioeconomic status did not. Findings support a theoretically grounded framework that underscores the importance of enhancing self-regulation and future orientation as person- centered strategies for suicide prevention among Filipino youth.